2011
DOI: 10.4103/1755-6783.85761
|View full text |Cite
|
Sign up to set email alerts
|

Dental health awareness, attitude, oral health-related habits, and behaviors in relation to socio-economic factors among the municipal employees of Mysore city

Abstract: Objective: To assess the dental health awareness, attitude, oral health-related habits, and behaviors in relation to socioeconomic factors among the municipal employees of Mysore city. Study Design and Methodology: This study was cross-sectional in nature and involved completion of a predesigned structured questionnaire. The questionnaire included multiple option questions to collect information on awareness on dental diseases, visit to dentist, reasons for visit, reasons for not visiting dentist on routine ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 26 publications
3
21
0
Order By: Relevance
“…Our study showed that 205 out of 206 participants were aware of dentistry as a profession, representing 95.5% of the study population. This findings is similar to the reports of Chandra et al [ 22 ] where 100% of participants of high socio economic status group claimed they are awareness of dental diseases. Similarly, Asif et al [ 18 ] also found that 89.9% of their study population knew that there were 32 teeth in the adult cavity.…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed that 205 out of 206 participants were aware of dentistry as a profession, representing 95.5% of the study population. This findings is similar to the reports of Chandra et al [ 22 ] where 100% of participants of high socio economic status group claimed they are awareness of dental diseases. Similarly, Asif et al [ 18 ] also found that 89.9% of their study population knew that there were 32 teeth in the adult cavity.…”
Section: Discussionsupporting
confidence: 91%
“…[16] Similar to the findings of Parveen et al .,[3] the present study also revealed that about three-fourth of the subjects were aware of the harmful effects of excess sweet, cold drinks, alcohol consumption, and smoking/pan chewing/gutkha and other tobacco products on oral hygiene. However, Chandrashekhar B R et al .…”
Section: Discussionsupporting
confidence: 90%
“…Adolescents from such families are more susceptible to oral conditions that can negatively influence QOL, such as poorer oral health; in other words, they have a greater experience of caries and periodontal disease [ 8 , 26 , 43 – 45 ]. In addition, some authors have noted that socioeconomic conditions are directly related to the presence of harmful oral habits, which could influence the development of malocclusion [ 46 ].…”
Section: Discussionmentioning
confidence: 99%